Culture Contacts and Linguistic Hybridity - Esteban, Rolando (Linguae et Litterae, 2010)
The juxtapositioning of one language community with another is a feature of a culturally-diverse country like the Philippines. In Mindanao, this partly resulted from culture contacts in historical times. It began in the 1860s with the efforts of the Jesuits to settle new Christians among the indigenous peoples into agricultural villages on the plains (Arcilla 1990). The Americans followed it up from 1904 to 1913 by settling first the Muslims and the indigenous peoples near the plantations on the island (Esteban 1991). Then migrants from Luzon and the Visayas came into agricultural colonies from 1913 to 1935 The settlement of Mindanao intensified from 1935 to 1941, when the commonwealth government relocated homesteaders from Luzon and the Visayas to the still uncolonized districts of the island (Esteban, 2004a).